2011
DOI: 10.4025/actasciagron.v33i4.11084
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of torch ginger inflorescences with 1-methylcyclopropene and preservative solutions

Abstract: ABTRACT. This work aimed at the assessment of the influence of 1-MCP on ethrel action and on its association with preservative solutions on torch ginger. In the first experiment, the inflorescences were pre-treated with 1-MCP in sealed chambers at concentrations of 0, 1, 1.5, and 2.0 g m -3, for 24 hours. Later, the inflorescences were submitted to the treatment with ethrel (100 μL L -1 ) in sealed chamber for 24 hours. In the second experiment, the inflorescences were pre-treated with 1.5 g m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Similar searches of Unemoto et al (2011), in a post-harvest study of the torch ginger also observed a reduction in fresh weight over time after harvest.…”
Section: Resultsmentioning
confidence: 60%
“…Similar searches of Unemoto et al (2011), in a post-harvest study of the torch ginger also observed a reduction in fresh weight over time after harvest.…”
Section: Resultsmentioning
confidence: 60%
“…Massa fresca relativa (%) das hastes florais de bastão-do-imperador em função de dias após a colheita (DAC) comparando-se os diferentes estádios de abertura floral. Unemoto et al (2011), em estudo pós-colheita com bastão-do-imperador, observaram variações na massa fresca entre 11% a 30%, ao longo de 15 dias de avaliação, sendo que nas hastes tratadas apenas com água ocorreu uma perda de 16%. A perda excessiva de massa fresca (água) pela transpiração e/ou obstruções dos vasos do xilema, causam murcha e, consequentemente, redução da durabilidade pós-colheita.…”
Section: Resultsunclassified
“…de Araújo et al (2018) proposed that cultivar IAC 41 and IAC Camburi were chosen as the suitable cultivars for the breeding program based on their flower appearance and vase life where 8 and 5 days were observed, respectively. On a positive note, application of 1-Methylcyclopropene (1-MCP) and Florissant® were reported to be successful in prolonging the durability of the blooming inflorescence up to five days (Bayogan & Gratuito, 2015;Unemoto, de Faria, Takahashi, de Assis, & Lone, 2011).…”
Section: Development Of New Cultivars Through Breeding Programmementioning
confidence: 99%